2016
DOI: 10.1016/j.est.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale integration of renewable energies and impact on storage demand in a European renewable power system of 2050—Sensitivity study

Abstract: Driven by decreasing prices for photovoltaic (PV) systems and incentive programs of different governments, almost 100 GW of PV and over 100 GW of wind turbines (WT) have been integrated in the European power system by 2014. In some areas, the electricity generation already exceeds the demand, curtailing generation or pushing the existing power transmission infrastructure to its limits in certain hours. In order to reach the European Commission's targets for 2050, the integration of renewable energies will requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(67 citation statements)
references
References 11 publications
1
65
0
1
Order By: Relevance
“…cold TES and solar PV technologies together. In general, by the increase of solar PV share higher short-term TES is required which is also consistent with findings of other researchers[80]. In other words, the higher the dependency of energy system on the solar PV, the higher the storage is needed to ensure the security of electricity supply of the system without intermittency and hence avoid possible penalties.For instance, in case of using 1500 kWh of TES a total annual savings of 8945 € could be achieved.…”
supporting
confidence: 90%
“…cold TES and solar PV technologies together. In general, by the increase of solar PV share higher short-term TES is required which is also consistent with findings of other researchers[80]. In other words, the higher the dependency of energy system on the solar PV, the higher the storage is needed to ensure the security of electricity supply of the system without intermittency and hence avoid possible penalties.For instance, in case of using 1500 kWh of TES a total annual savings of 8945 € could be achieved.…”
supporting
confidence: 90%
“…Like the need for the energy capacity of the storage devices rises with increasing share of RES penetration, so does the need for storage power. Using a holistic model with a hierarchical management approach, Bussar et al recently found that a renewable power supply system for the EU-MENA region (Europe, Middle East and North Africa) would be most economic with a combination of storage devices having a total discharging power on the same order as the peak load, whereupon long-term storage was also found to need higher charging power than discharging power [19]. Furthermore, the discharge power of the long-term storage was found to be higher than the combined discharge power of both short-term and medium-term storage [19], which stresses the importance of long-term storage in future power systems based on (V)RES.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these simplifications, the results of the analysis are considered optimistic in terms of the power system's ability to dispatch energy, and will therefore overestimate the capacity to accommodate renewable energy production. On the other hand, PowerGAMA takes the physical power flow into account, which is a significant advantage over the power market simulators that only consider energy balance, such as the EMPS 3 model. An in-depth explanation of how PowerGAMA works is given in the PowerGAMA User…”
Section: Underlying Assumptions and Simplification In Powergamamentioning
confidence: 99%
“…Where equations (2)(3)(4)(5) are the constraints that delimit the variables. From the DC power flow equations [10], we have the power flow constraint (6), which describes the flow in the AC branches only.…”
Section: Mathematical Formulation Of Powergamamentioning
confidence: 99%